2020
DOI: 10.1177/1747954120973101
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying jump-specific loads in beach volleyball by an inertial measurement device

Abstract: The ability to complete a large volume of high intensity jumps represents an important performance indicator in beach volleyball. Inertial measurement units are suitable tools to monitor those jump-specific loads but the applicability in beach volleyball lacks research. This study evaluates the accuracy of a commercially available inertial measurement device in beach volleyball for (i) jump count during match-play and (ii) jump height measurement under laboratory conditions. Jump count measures were compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 22 publications
3
14
0
Order By: Relevance
“…These large LoA values exceed the acceptable range for high-level performance diagnostics in sports and the accurate interpretation of test results following training or intervention. The findings align with those of Schmidt et al (35), reporting a LoA of 15.3 cm for volleyball block jumps and 13.2 cm for attack jumps. An individual analysis by Schmidt et al (35) revealed a broad range of LoA for individual subjects.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These large LoA values exceed the acceptable range for high-level performance diagnostics in sports and the accurate interpretation of test results following training or intervention. The findings align with those of Schmidt et al (35), reporting a LoA of 15.3 cm for volleyball block jumps and 13.2 cm for attack jumps. An individual analysis by Schmidt et al (35) revealed a broad range of LoA for individual subjects.…”
Section: Discussionsupporting
confidence: 91%
“…The findings align with those of Schmidt et al (35), reporting a LoA of 15.3 cm for volleyball block jumps and 13.2 cm for attack jumps. An individual analysis by Schmidt et al (35) revealed a broad range of LoA for individual subjects. A possible factor could be different performance levels and resulting jumping techniques of subjects (sixth to first German division); moreover, specific jumping techniques (block and spike) might also play a role compared with conventional jumps.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In general, a good vertical jumping performance is of major importance for BV players since vertical jumping is present in the majority of the skills of the sport [ 29 , 30 , 31 , 32 ]. However, past research reported differences concerning vertical jumping on SAND compared to RIGID [ 29 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies has measured vertical jump performance on SAND using jump and reach tests [ 19 , 21 , 29 , 31 ]. Other researchers provided information about jumping on SAND using photocell mats [ 10 ], accelerometry [ 15 ] and inertial measurement devices [ 32 ]. Kinetic and kinematic parameters derived from force-plate data have been reported only for SQJ and CMJ [ 33 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%